The conditional impact of market consolidation and market power on banking stability – Evidence from Europe - Herwald, Sarah; Voigt, Simone; Uhde, André (Journal of Risk Finance)
Purpose Academic research has intensively analyzed the relationship between market concentration or market power and banking stability but provides ambiguous results, which are summarized under the concentration-stability/fragility view. We provide empirical evidence that the mixed results are due to the difficulty of identifying reliable variables to measure concentration and market power. Design/methodology/approach Using data from 3,943 banks operating in the European Union (EU)-15 between 2013 and 2020, we employ linear regression models on panel data. Banking market concentration is measured by the Herfindahl–Hirschman Index (HHI), and market power is estimated by the product-specific Lerner Indices for the loan and deposit market, respectively. Findings Our analysis reveals a significantly stability-decreasing impact of market concentration (HHI) and a significantly stability-increasing effect of market power (Lerner Indices). In addition, we provide evidence for a weak (or even absent) empirical relationship between the (non)structural measures, challenging the validity of the structure-conduct-performance (SCP) paradigm. Our baseline findings remain robust, especially when controlling for a likely reverse causality. Originality/value Our results suggest that the HHI may reflect other factors beyond market power that influence banking stability. Thus, banking supervisors and competition authorities should investigate market concentration and market power simultaneously while considering their joint impact on banking stability.
Keywords: market concentration; market power; banking stability; European banking

The conditional impact of market consolidation and market power on banking stability – Evidence from Europe - Herwald, Sarah; Voigt, Simone; Uhde, André

Risk allocation through securitization – Evidence from non-performing loans - Wengerek, Sascha Tobias; Hippert, Benjamin; Uhde, André (The Quarterly Review of Economics and Finance)
Employing a unique and hand-collected sample of 648 true sale loan securitization transactions issued by 57 stock-listed banks across the EU-12 plus Switzerland over the period from 1997 to 2010, this paper empirically analyzes the relationship between true sale loan securitization and the issuing banks’ non-performing loans to total assets ratios. Overall, we provide evidence for a negative impact of securitization on NPL exposures suggesting that banks predominantly used securitization as an instrument of credit risk transfer and diversification. In addition, the analysis at hand reveals a time-sensitive relationship between securitization and NPL exposures. While we observe an even stronger NPL-reducing effect through securitization during the non-crisis periods, the effect reverses during and after the global financial crisis suggesting that banks were forced to provide credit enhancement and employ securitization as a funding management tool. Along with the results from a variety of sensitivity analyses our study provides important implications for the recent debate on reducing NPL exposures of European banks by revitalizing the European securitization market.
Keywords: European Banking; Non-performing Loans; Securitization

Semiparametric GARCH models with long memory applied to Value at Risk and Expected Shortfall - Letmathe, Sebastian; Feng, Yuanhua; Uhde, André (Journal of Risk)
In this paper new semiparametric generalized autoregressive conditional heteroscedasticity (GARCH) models with long memory are introduced. A multiplicative decomposition of the volatility into a conditional component and an unconditional component is assumed. The estimation of the latter is carried out by means of a data-driven local polynomial smoother. According to the revised recommendations by the Basel Committee on Banking Supervision to measure market risk in the banks’ trading books, these new semiparametric GARCH models are applied to obtain rolling one-step ahead forecasts for the value-at-risk and expected shortfall (ES) for market risk assets. Standard regulatory traffic-light tests and a newly introduced traffic-light test for the ES are carried out for all models. In addition, model performance is assessed via a recently introduced model selection criterion. The practical relevance of our proposal is demonstrated by a comparative study. Our results indicate that semiparametric long-memory GARCH models are a meaningful substitute for their conventional, parametric counterparts.
Keywords: long memory; generalized autoregressive conditional heteroscedasticity (GARCH) models; value-at-risk (VaR); expected shortfall (ES); traffic-light test; backtesting

Tax avoidance through securitization - Uhde, André (The Quarterly Review of Economics and Finance)
Employing a unique hand-collected sample of 956 credit risk securitization transactions issued by 64 stock-listed European banks across the EU-13 plus Switzerland over the period from 1997 to 2010, this paper empirically analyzes the impact of securitization on the issuing banks’ effective tax rates. Our analysis reveals that banks may reduce their tax expense through securitization via a direct and indirect channel suggesting that tax avoidance may be a further motive for banks to engage in the securitization business. These baseline findings remain robust under various robustness checks, especially when implementing structural equation models and controlling for a reverse causality between the banks’ tax burden and their incentive to securitize. Finally, various sensitivity analyses provide further important results and implications for tax policies, banking regulation and the ongoing process of revitalizing the European securitization market.
Keywords: Securitization; Credit risk transfer; Effective tax rates; European banking

CDS Investors’ Risk Perceptions of M&A Announcements - Hippert, Benjamin; Uhde, André
Merging a sample of 492 merger and acquisition (M&A) announcements from 284 acquiring firms across Europe and North America with data from 5-year single-name credit default swaps (CDSs) written on stock-listed acquiring firms between 2005 and 2018, the paper at hand empirically analyzes the CDS investors’ risk perceptions of M&A announcements using event study methodologies. As a baseline result, we provide evidence for significantly positive cumulative average abnormal CDS spread changes for both, European and North American acquirers suggesting that CDS investors perceive an increase in the acquiring firms’ credit risk exposures due to M&A announcements. Our baseline finding holds under several robustness checks, especially when controlling for the robustness of the empirical design. Moreover, results from a large variety of sensitivity analyses reveal a number of deal and firm characteristics that may explain why CDS investors from our sample expect an increase in the acquirers’ credit risk exposures due to forthcoming M&A transactions.
Keywords: credit default swaps; risk perception of CDS investors; mergers and acquisitions; event study

Determinants of CDS Trading on Major Banks - Hippert, Benjamin; Uhde, André; Wengerek, Sascha Tobias
This paper empirically investigates determinants of the outstanding net notional amount of credit default swaps (CDSs) contracts written on banks. We extend and complement the previous literature dealing with CDS trading by analyzing a comprehensive set of CDS tradingspecific, bank-fundamental, macroeconomic and bank-institutional determinants. We find that risk hedging clearly dominates an investor’s speculation and arbitrage motive, while the latter, however, exhibits the strongest impact on the outstanding net notional amount of bank CDSs. Furthermore, being classified as a G-SIB, being a constituent of the main CDS index and the equity trading volume may significantly explain changes in the outstanding CDS net notional on banks. The analysis at hand provides important implications for both academics and practitioners, since understanding the trading motives of bank CDS investors provides a deeper insight into the opaque CDS market.
Keywords: banking; outstanding CDS net notional; determinants of bank CDS trading

The relationship between announcements of complete mergers and acquisitions and acquirers' abnormal CDS spread changes - Hippert, Benjamin
Employing a sample of 492 merger and acquisition (M&A) announcements from 284 acquirers across North America and Europe between 2005 and 2018, this study analyzes the impact of M&A announcements on an acquirers abnormal CDS spread changes. We find that spreads from CDS which are written on acquirers increase by 310 bps during a symmetric five-day event window suggesting that investors expect an increase in the acquirers credit risk exposure due to M&As. Next to this baseline finding, we conduct a large variety of sensitivity analyses to gain more insight into the driving factors of the rising risk perception of CDS investors due to M&A announcements.
Keywords: credit default swaps; risk perception of CDS investors; mergers and acquisitions; event study

Portfolio Benefits of Adding Corporate Credit Default Swap Indices: Evidence from North America and Europe - Hippert, Benjamin; Uhde, André; Wengerek, Sascha Tobias (Review of Derivatives Research)
Employing main and sector-specific investment-grade CDS indices from the North American and European CDS market and performing mean-variance out-of-sample analyses for conservative and aggressive investors over the period from 2006 to 2014, this paper analyzes portfolio benefits of adding corporate CDS indices to a traditional financial portfolio consisting of stock and sovereign bond indices. As a baseline result, we initially find an increase in portfolio (downside) risk-diversification when adding CDS indices, which is observed irrespective of both CDS markets, investor-types and different sub-periods, including the global financial crisis and European sovereign debt crisis. In addition, the analysis reveals higher portfolio excess returns and performance in CDS index portfolios, however, these effects clearly differ between markets, investor-types and sub-periods. Overall, portfolio benefits of adding CDS indices mainly result from the fact that institutional investors replace sovereign bond indices rather than stock indices by CDS indices due to better risk-return characteristics. Our baseline findings remain robust under a variety of robustness checks. Results from sensitivity analyses provide further important implications for institutional investors with a strategic focus on a long-term conservative portfolio management.
Keywords: Corporate credit default swap indices; Mean-variance asset allocation; Out-of-sample portfolio optimization; Portfolio risk-diversification; Portfolio performance evaluation

Share price reactions to tariff imposition announcements in the Trump era – An event study of the trade conflict - Wengerek, Sascha Tobias; Uhde, André
Employing a unique sample of 2,849 tariff imposition announcements by and against the United States (U.S.) over the period from 2018 to 2019, this study analyzes the impact of recent tariff announcements on share prices from 859 U.S. companies. We provide evidence for negative (cumulative) average abnormal stock returns due to tariff announcements during a symmetric three-day event window. We suggest that stock market investors expect adverse impacts of tariff impositions, e.g. a decrease in the companies' future cash flows and a threat of retaliation. The negative wealth effects are observed irrespective of whether the Trump administration announces safeguard tariffs to protect domestic firms or a retaliation is declared by foreign countries. Moreover, building several subsamples, we find that the adverse impact is mostly driven by announcements involving China and is associated with a variety of sector, tariff, trade and firm characteristics.
Keywords: event study; international relations; protectionism; strategic trade policy; tariffs; trade conflict

Determinants of CDS trading on major banks - Hippert, Benjamin; Uhde, André; Wengerek, Sascha Tobias
Employing credit default swap (CDS) data for a sample of 52 major banks across 18 countries from 2008 to 2016, this paper investigates determinants of the outstanding net notional amount of CDS which are written on banks. We extend the current literature dealing with CDS trading by analyzing further CDS trading-specific, fundamental bank-specific as well as macroeconomic and institutional determinants with a focus on bank CDS trading. We find that, next to well-discussed determinants for corporate firms in the literature, especially a bank's tail risk, capital adequacy, loan portfolio and business model affect a bank's outstanding CDS net notional. This finding indicates that investors in the bank CDS market partly have a recourse to a fundamental analysis for their investment decision. Our study fills an important gap since empirical studies have solely focused on sovereign and corporate CDS yet. In addition, the analysis at hand provides important implications for both academics and practitioners since understanding the trading motives of bank CDS investors gives deeper insights into the still opaque CDS market.
Keywords: banking; outstanding CDS net notional; determinants of bank CDS trading

Determinants of CDS trading on major banks - Hippert, Benjamin; Uhde, André
Employing credit default swap (CDS) data for a sample of 52 major banks across 18 countries from 2008 to 2016, this paper investigates determinants of the outstanding net notional amount of CDS which are written on banks. We extend the current literature dealing with CDS trading by analyzing further CDS trading-specifi c, fundamental bank-speci fic as well as macroeconomic and institutional determinants with a focus on bank CDS trading. We fi nd that, next to well-discussed determinants for corporate firms in the literature, especially a bank's tail risk, capital adequacy, loan portfolio and business model affect a bank's outstanding CDS net notional. This finding indicates that investors in the bank CDS market partly have a recourse to a fundamental analysis for their investment decision. Our study fills an important gap since empirical studies have solely focused on sovereign and corporate CDS yet. In addition, the analysis at hand provides important implications for both academics and practitioners since understanding the trading motives of bank CDS investors gives deeper insights into the still opaque CDS market.
Keywords: banking; outstanding CDS net notional; determinants of bank CDS trading

Restrukturierungen: operative und finanzielle Wertbeiträge. Eine Betrachtung vor dem Hintergrund der Entwicklungen bei thyssenkrupp - Sievers, Sönke; Sureth-Sloane, Caren; Uhde, André (Die Wirtschaftsprüfung)
Restrukturierungen werden sowohl durch die Digitalisierung, aber auch durch klassische Themen – beispielsweise die Notwendigkeit von Umsatz- und Kostensynergien in kompetitiven Märkten – verstärkt vorangetrieben. Dieser Beitrag beleuchtet vor allem die Motive und Folgen aus wissenschaftlicher Perspektive, indem großzahlige empirische Befunde zu den Themen Beschäftigung, Finanzkennzahlen und Kapitalerhöhungen sowie steuerliche Motive prägnant zusammengefasst und im Kontext des geplanten Joint Ventures von thyssenkrupp und Tata Steel diskutiert werden.

Restrukturierungen: operative und finanzielle Wertbeiträge. Eine Betrachtung vor dem Hintergrund der Entwicklungen bei thyssenkrupp - Sureth-Sloane, Caren; Sievers, Sönke; Uhde, André (Die Wirtschaftsprüfung)
Restrukturierungen werden sowohl durch die Digitalisierung, aber auch durch klassische Themen – beispielsweise die Notwendigkeit von Umsatz- und Kostensynergien in kompetitiven Märkten – verstärkt vorangetrieben. Dieser Beitrag beleuchtet vor allem die Motive und Folgen aus wissenschaftlicher Perspektive, indem großzahlige empirische Befunde zu den Themen Beschäftigung, Finanzkennzahlen und Kapitalerhöhungen sowie steuerliche Motive prägnant zusammengefasst und im Kontext des geplanten Joint Ventures von thyssenkrupp und Tata Steel diskutiert werden.

Unternehmerische Finanzierungspolitik - Paul, Stephan; Horsch, Andreas; Kaltofen, Daniel; Uhde, André; Weiß, Gregor
Nach der Finanzkrise sind die Modellwelten der Finanzierungstheorie, vor allem diejenigen, die auf vollkommenen Märkten spielen, nicht mehr zeitgemäß. Heute muss die Lehre zu Theorie und Praxis der Finanzierungspolitik beide Sphären miteinander verbinden - wie es das Konzept dieses neuen Lehrbuchs verfolgt: Aus der strategischen Sicht des Finanzleiters werden die zentralen Themen der unternehmerischen Finanzierungspolitik aufgezeigt: Investitionsrechnung, Nutzung von Finanzmärkten, -intermediären und -instrumenten, Finanzielles Risikomanagement, Finanzkommunikation, Gestaltung von Unternehmensstruktur und -kontrolle. Mit vielen Anwendungsbeispielen und Einblicken in die Praxis.
Keywords: Investitionsrechnung; finanzielles Risikomanagement; Finanzkommunikation

The relationship between credit risk transfer and non-performing loans. Evidence from European banks - Uhde, André; Wengerek, Sascha Tobias
Employing a unique and hand-collected sample of 648 true sale loan securitization transactions issued by 57 stock-listed banks across the EU-12 plus Switzerland over the period from 1997 to 2010, this paper empirically analyzes the relationship between true sale loan securitization and the issuing banks' non-performing loan to total assets ratios (NPLRs). We provide evidence for an NPLR-reducing effect during the boom phase of securitizations in Europe suggesting that banks in our sample may (partly) securitize NPLs as the most risky junior tranche and do not (fully) retain NPLs as a reputation and quality signal towards less informed investors in imperfect capital markets. In contrast, we fi nd the reverse effect during the crises period in Europe indicating that issuing banks provided credit enhancement and demonstrated `skin in the game'. Our baseline result remains robust when controlling for endogeneity concerns and a potential persistence in the time series of the NPL data. Moreover, results from a variety of sensitivity analysis reveal that the NPLR-reducing effect is stronger for opaque securitization transactions, for issuing banks exhibiting higher average levels of NPLRs and for banks operating from non-PIIGS countries. In addition, a reduction of NPLRs through securitization is observed for issued collateralized debt obligations, residential mortgage-backed securities, consumer and other unspeci ed loans as well as for non-frequently issuing, systemically less important and worse-rated banks. Our analysis offers essential insights into the loan risk allocation process through securitization and provides important implications for the vital debate on reducing NPL exposures and the process of revitalizing and regulating the European securitization market.
Keywords: European Banking; Non-performing Loans; Risk Allocation; Securitization

Risk-taking incentives through excess variable compensation: Evidence from European banks - Uhde, André (The Quarterly Review of Economics and Finance)
Employing compensation data provided by 63 banks from 16 European countries for the period from 2000 to 2010 this paper empirically investigates the impact of excess variable compensation on bank risk. As a main finding, we provide evidence for a risk-increasing impact of excess variable pay for both executive variable cash-based and variable equity-based compensation. This baseline finding holds under various robustness checks, in particular when controlling for likely reverse causality between bank risk and variable compensation by employing Granger-causality tests and instrumental variable regressions. In addition, results from a large number of sensitivity analyses including board and banking characteristics as well as the financial crisis period and the quality of a country's regulatory framework provide further important implications for banking regulators and politicians in Europe.
Keywords: Banking; Executive compensation; Risk-taking; Financial stability

Determinants of loan securitization in European banking - Farruggio, Christian; Uhde, André (Journal of Banking and Finance)
Analyzing 75 securitizing and non-securitizing stock-listed banks in the EU-13 plus Switzerland over the period from 1997 to 2010, this paper provides empirical evidence that loan securitization in Europe is a composite decision based on bank-specific as well as market- and country-specific determinants. In addition, we find that these determinants remarkably change when separately investigating securitization transactions during the pre-crisis and crisis period. Moreover, results from several subsample regressions reveal that determinants of loan securitizations in Europe depend on the transaction type, the underlying asset portfolio and the regulatory and institutional environment under which banks operate.
Keywords: Securitization; Determinants; European banking

External governance outcome and microfinance success - Uhde, André; Müller, Oliver (International Journal of Monetary Economics and Finance)
Employing a Hausman–Taylor instrument variable (HT–IV) estimator to data from 558 microfinance institutions (MFIs) in 80 developing countries for the period from 2002 to 2007, this paper provides empirical evidence for a positive impact of a country's external governance quality and outcome on local microbanks' economic success in terms of profitability and sustainability. Evidence as well suggests a negative relationship between external governance and the microbanks' social success measured by the depth of outreach. In this context, our analysis reveals that a country's political stability, governance effectiveness, regulatory quality and rule of law are significant key elements of external governance affecting the MFIs' functional performance. Moreover, results from sensitivity analyses indicate that the relationship between external governance quality and microfinance functional performance significantly depends on the microbanks' business concepts, their lending methodologies and sources of funding.
Keywords: microfinance; external governance; economic success; social success; developing countries; profitability; sustainability; microbanks; outreach; political stability; governance effectiveness; regulatory quality; rule of law; governance quality; lending methodologies; funding sources

The light and dark side of TARP - Farruggio, Christian; Michalak, Tobias C.; Uhde, André (Journal of Banking and Finance)
Employing four event dates of the U.S. “Troubled Asset Relief Program” (TARP) this paper empirically investigates the impact of the first announcement of TARP (September 19, 2008), the announcement of revised TARP (October 14, 2008), respective capital infusions under TARP-CPP and capital repayments on changes in shareholder value and risk exposure of 125 supported U.S. banks as perceived by the capital market through share price reactions for an entire sample period from September 19, 2008 to June 16, 2010. Our analysis reveals a light and a dark side of TARP. While announcements as well as capital repayments may restore market confidence and financial stability, equity capital injections to banks are observed to be a severe impediment to an increase in bank shareholder value and financial soundness.
Keywords: Financial crisis; TARP; Market efficiency; Event study

Credit risk securitization and bank soundness: Evidence from the microlevel for Europe - Michalak, Tobias C.; Uhde, André (Quarterly Review of Economics and Finance)
Using a unique sample of 749 cash and synthetic securitization transactions issued by 60 stock-listed bank holdings in the EU-13 plus Switzerland over the period from 1997 to 2007 this paper provides empirical evidence that credit risk securitization has a negative impact on the issuing banks’ financial soundness. Baseline findings hold even when controlling for likely reverse causality by employing instrumental variable techniques and substituting the accounting-based z-score ratio by market-based indicators of bank risk. Moreover, investigating the relationship between credit risk securitization and single z-score components in order to evaluate significant transmission channels proposed by relevant theoretical literature, we find a negative impact of securitization on bank profitability and capital environment as well as a positive relationship between securitization and the issuing bank's return volatility. Against the background of our empirical results we underline that the decision by the Basel Committee to enhance the new Basel III framework in the field of securitization is a step in the right direction.
Keywords: Credit risk securitization Bank soundness European banking

Cross-border bank lending - Empirical evidence on further determinants from OECD banking markets - Müller, Oliver; Uhde, André (Journal of International Financial Markets, Institutions & Money)
Employing data on foreign bank claims from 13 OECD countries on 51 emerging markets between 1993 and 2007, this study investigates specific characteristics of OECD banking markets and lending banks as new important determinants of cross-border lending. We initially provide empirical evidence that in addition to well-accepted “gravity measures”, characteristics of OECD banking markets as well as lending banks’ attributes may describe further important determinants of cross-border bank lending with regard to our sample. Building subsamples of more-developed emerging markets vs. frontier markets, addressing (non) common lender relationships and analyzing cross border lending flows during different time periods, our analysis additionally reveals that both the determinants’ explanatory power and their direction of impact notably vary with respective subsamples.
Keywords: Foreign bank claims; Gravity measures; OECD banking markets’ characteristics; Lending banks’ characteristics

Wealth effects of credit risk securitization in European Banking - Farruggio, Christian; Michalak, Tobias C.; Uhde, André (Journal of Business Finance and Accounting)
Using a unique cross‐sectional dataset of 381 cash and synthetic securitizations issued by 53 banks from the EU‐15 plus Switzerland between 1997 and 2007, this paper provides empirical evidence for time‐dependent negative wealth effects of credit risk securitization announcements in European banking. Baseline results hold when comparing estimated wealth effects with a control group of similar but non‐securitizing banks for the relevant time period. Moreover, building several sub samples we find that the nexus between credit risk securitization, the issuing banks’ overall risk exposure and wealth effects is associated with a variety of transaction‐ and bank‐specific factors.
Keywords: wealth effects; credit risk securitization; Europe; event study

Measuring the quality of banking supervision revisited - Assessments by German banks before and during the financial crisis - Paul, Stephan; Stein, Stefan; Uhde, André (Journal of Governance and Regulation)
This contribution presents and discusses main results of a new survey on the assessment of supervisory quality among German banks in 2010. In particular, it is analyzed if and how supervised banks’ perception of the quality of supervisory authorities and their instruments has changed due to the financial crisis starting in mid-2007. Subsequently, results from the recent survey are compared with findings provided by a former study carried out by the authors in 2006 (Paul, Stein and Uhde, 2008).
Keywords: banking supervision; quality; assessment; banking sector

Sovereign Risk and Bank-Specific CDS Pricing - Meine, Christian; Michalak, Tobias C.; Uhde, André
Employing time series of single-name CDS market spreads from 29 European banks located in the EU-12 plus Switzerland and the UK over the period from January 2004 through September 2010 this paper analyses the relationship between increasing sovereign risk and bank-specific CDS pricing. Results from calculating relative CDS spread deviations (model minus market spreads) initially reveal a price bubble in the European CDS market until the beginning of the financial crisis in mid-2007. From this point in time the gap narrows remarkably during the financial crisis and sovereign debt crisis period. Corresponding to these findings, the empirical analysis reveals a negative impact of sovereign risk on calculated CDS spread differentials indicating a spill-over effect between sovereign risk and bank risk and hence, a positive effect on bank-specific CDS pricing. Further analyses reveal that the perception of sovereign risk is not crisis- but country-dependent suggesting that bank-specific CDS market spreads may already include a premium to cover sovereign risk from PIIGS countries during the pre-crisis period in Europe.
Keywords: Sovereign risk; Structural credit risk models; bank-specific CDS pricing

Zur Neuregulierung des Bankensektors nach der Finanzkrise: Bewertung der Reformvorhaben der EU aus ordnungspolitischer Sicht - Haucap, Justus; Heimeshoff, Ulrich; Uhde, André (Die aktuelle Finanzkrise: Bestandsaufnahme und Lehren für die Zukunft, Schriften zur Ordnungsfragen der Wirtschaft)
Im Zuge der in den USA durch die exzessive Vergabe von Subprime-Krediten und deren Verbriefung ausgelöste Finanzkrise und der daraus folgenden weltweiten Wirtschaftskrise hat sich gezeigt, dass das bisherige System der Regulierung bzw. Überwachung von Finanzinstitutionen nicht ausreichend ist. Sowohl in den USA als auch in der Europäischen Union wird deshalb intensiv über ein neues System zur Regulierung von Finanzinstituten nachgedacht. Es ist zwar offen-sichtlich, dass eine wesentliche Ursache der Finanzkrise in den USA die Ermunterung der Finanzinstitute durch den Staat zur Vergabe von Immobilienkrediten an nicht ausreichend solvente Konsumenten war. Die vorhandenen Regulierungsinstrumente konnten die Krise jedoch nicht verhindern bzw. ausreichen abmildern. Das vorliegende Papier setzt sich zum Ziel, die Vorschläge zur Reform der Bankenregulierung zu evaluieren und insbesondere auf ihre potenziellen Wirkungen im Hinblick auf den Wettbewerb im Bankensektor zu überprüfen. Im Zuge der Diskussion über mögliche Lösungen existieren verschiedenste Vorschläge, die von Änderungen in Rechnungslegungsvorschriften über die Neuordnung der nationalen bzw. internationalen Finanzaufsicht bis hin zu einer stärkeren Berücksichtigung systemischer Risiken gehen. Die Auswirkungen der Finanzkrise haben gezeigt, dass die Abkehr von herkömmlichen Rechnungslegungssystemen hin zu Regeln der internationalen Rechnungslegung unter dem Schlagwort „Fair Value Accounting“ durchaus Gefahren in sich bergen kann. Die Debatte dreht sich insbesondere um die Frage, ob die neuen Rechnungslegungsvorschriften maßgeblich dazu beitragen, das regulatorische Eigenkapital einer Bank in Boomphasen zu erhöhen und in konjunkturellen Schwächephasen dagegen zu senken. In der Literatur ist in Hinblick auf diese Frage bislang keine einhellige Auffassung zu identifizieren. Pellens et al. (2009) gelangen zu dem Ergebnis, dass bankenaufsichtsrechtliche Normen an das IFRS-Zahlenwerk gebunden sind und dies für regulatorische Entscheidungen als besonders kritisch zu sehen ist. Durch das Konzept des Fair-Value-Accounting wurde das regulatorische Eigenkapital im Zeitraum von 2003 bis 2007 systematisch erhöht, woraus ein gestiegener Kreditvergabespielraum resultierte. Demgegenüber kommen Laux und Leuz (2009) im Rahmen einer empirischen Studie anhand von Mikrodaten aus den USA zu dem Ergebnis, dass Fair-Value-Accounting nur zum geringen Teil zu den Problemen der US Banken beigetragen hat und es im Rahmen ihrer Studie keine Evidenz für wesentliche Effekte dieses Rechnungslegungsverfahrens auf die massiven Abschreibungen der US Banken gibt. Beide Studien betonen aber auch, dass weitere empirische Forschung notwendig ist, bevor diese Frage abschließend geklärt werden kann. Die Frage des adäquaten Rechnungslegungssystems zeigt, wie vielfältig die Ursachen der gegenwärtigen Finanzkrise sind und wie schwer tatsächliche kausale Effekte zu identifizieren sind. Im folgenden Abschnitt werden zunächst die ordnungspolitischen Rahmenbedingungen einer angemessenen Bankenregulierung dargestellt. Der dritte Abschnitt umfasst einen kurzen Überblick über den Verlauf der Finanzkrise. In Abschnitt 4 diskutieren wir die wesentlichen Vorschläge zur Optimierung der Regulierung von Finanzinstituten. Abschnitt 5 evaluiert diese Vorschläge auch aus einer wettbewerbsökonomischen Perspektive. Diese Perspektive ist aus unserer Sicht vor allen Dingen notwendig, weil eine großer Teil der Reformdebatte aus Sicht der Finanzmarktstabilität geführt wird und infolgedessen Wettbewerbseffekte vernachlässigt werden. Das Fazit in Abschnitt 6 fasst unsere Ergebnisse zusammen und gibt einen Ausblick auf weiteren Forschungsbedarf aus Sicht der Wettbewerbsökonomie.

Ökonomische Möglichkeiten und Auswirkungen von Wettbewerb bei Zentralverwahrern für Bundeswertpapiere. Gutachten im Auftrag des Bundesministeriums für Finanzen (BMF). Gutachten fg 1/10 - Uhde, André; Haucap, Justus; Heimeshoff, Ulrich

The nexus between monetary policy, banking market structures and bank risk-taking - Uhde, André; Michalak, Tobias
Using a sample of stock-listed bank holding companies located in Western Europe over the period from 1997 to 2008 this paper provides empirical evidence that an increase in short-term interest rates as well as an extended period of expansionary monetary policy has a negative impact on European stock-listed banks’ soundness as measured by the Expected Default Frequency. Against this background and in order to evaluate interactions between the risk-taking channel of monetary policy and the competitiveness of a country’s banking market we find a negative impact of an increase in competition in the loan market – proxied by the Boone-indicator – on financial soundness. Referring to the structural-conduct performance (SCP) paradigm, this paper provides further evidence that an increase in concentration in the banking market spurs financial soundness.

The Nexus between Monetary Policy, Banking Market Structure and Bank Risk Taking - Michalak, Tobias C.; Uhde, André
Using a sample of stock-listed bank holding companies located in Western Europe over the period from 1997 to 2008 this paper provides empirical evidence that an increase in short-term interest rates as well as an extended period of expansionary monetary policy has a negative impact on European stock-listed banks’ soundness as measured by the Expected Default Frequency. Against this background and in order to evaluate interactions between the risk-taking channel of monetary policy and the competitiveness of a country’s banking market we find a negative impact of an increase in competition in the loan market – proxied by the Boone-indicator – on financial soundness. Referring to the structural-conduct performance (SCP) paradigm, this paper provides further evidence that an increase in concentration in the banking market spurs financial soundness.
Keywords: risk-taking channel; competition; concentration; bank soundness; European banking

Einheitlicher europäischer Bankenmarkt? Eine Einschätzung der Wettbewerbssituation vor und nach der Finanzkrise - Paul, Stephan; Uhde, André (Wirtschaftsdienst)
Die schwerste Finanz- und Wirtschaftskrise nach dem Zweiten Weltkrieg befindet sich nun schon in ihrem dritten Jahr und wird in weiten Teilen der Öffentlichkeit als Paradebeispiel für ein gravierendes Marktversagen eingestuft. Dies hat über die unmittelbaren staatlichen Rettungsmaßnahmen hinaus den Ruf nach "Mehr Staat in der Kreditwirtschaft!" verstärkt und vielfältige Vorschläge zur Ausweitung und Verschärfung der Beaufsichtigung der Banken hervorgerufen (zuletzt im September 2009 beim Finanzgipfel in Pittsburgh). Noch lässt sich nicht präzise genug abschätzen, welche staatlichen Hilfen für die Kreditwirtschaft erforderlich sein werden und welche Veränderungen in der Bankenregulierung noch vorgenommen werden müssen. Dennoch wird in diesem Beitrag der Versuch einer Skizze möglicher Auswirkungen auf die Wettbewerbssituation des europäischen und deutschen Bankenmarktes speziell im Retail-Segment unternommen. Um die durch die Finanzkrise hervorgerufenen Veränderungen einschätzen zu können, ist jedoch zunächst ein kurzer Blick auf die wichtigsten Etappen und Ergebnisse der europäischen Finanzmarktintegration erforderlich.
Keywords: Finanz- und Wirtschaftskrise; Bankenmarkt

Securitization and systematic risk in European banking: Empirical evidence - Uhde, André; Michalak, Tobias C. (Journal of Banking & Finance)
Using a unique dataset of 592 cash and synthetic securitizations issued by 54 banks from the EU-15 plus Switzerland over the period from 1997 to 2007 this paper provides empirical evidence that credit risk securitization has a positive impact on the increase of European banks’ systematic risk. Baseline results hold when comparing estimated beta coefficients with a control group of similar non-securitizing banks. Building several sub-samples we additionally find that (a) the increase in systematic risk is more relevant for larger banks that repeatedly engage in securitization, (b) securitization is more important for small and medium financial institutions, (c) banks have a higher incentive to retain the larger part of credit risk as a quality signal at the beginning of the securitization business in Europe, and (d) the overall risk-shifting effect due to securitization is more distinct when the pre-event systematic risk is low.
Keywords: Credit risk transfer; Securitization; Systematic risk; Event study

Consolidation in banking and financial stability in Europe: Empirical evidence - Uhde, André; Heimeshoff, Ulrich (Journal of Banking & Finance)
Using aggregate balance sheet data from banks across the EU-25 over the period from 1997 to 2005 we provide empirical evidence that national banking market concentration has a negative impact on European banks’ financial soundness as measured by the Z-score technique while controlling for macroeconomic, bank-specific, regulatory, and institutional factors. Furthermore, our analysis reveals that Eastern European banking markets exhibiting a lower level of competitive pressure, fewer diversification opportunities and a higher fraction of government-owned banks are more prone to financial fragility whereas capital regulations have supported financial stability across the entire European Union.
Keywords: Market structure; Financial stability; Banking regulation

Trennung von Netz und Betrieb als Königsweg? Pfadabhängigkeiten der Regulierung - Haucap, Justus; Heimeshoff, Ulrich; Uhde, André (BDI-Bundesnetzagentur-Regulierungskonferenz 2008)
Die Trennung von Netz und Betrieb steht nicht nur im Zentrum der politischen Debatte der Energiewirtschaft. Auch im Bahnsektor ist die Privatisierung mit oder ohne Netz ein heiß diskutiertes Thema. Und selbst in der Telekommunikation strebt die EU-Kommission eine weitgehende Entflechtung an. Der vorliegende Beitrag entwickelt anhand von ökonomischen Kriterien ein ideologiefreies Prüfschema, wann eine Entflechtung von Netz und Betrieb gesamtwirtschaftlich vorteilhaft ist und wann nicht.

Regulierung und Wettbewerbsrecht in liberalisierten Netzindustrien aus institutionenökonomischer Perspektive - Haucap, Justus; Uhde, André (Jahrbuch für die Ordnung von Wirtschaft und Gesellschaft)
Sowohl die Telekommunikationsbranche als auch die Elektrizitätswirtschaft haben in den vergangenen 10 Jahren in Kontinentaleuropa einen drastischen Wandel ihres ordnungspolitischen Rahmens erlebt. Während sich jedoch in der Telekommunikation die Ausgestaltung des ordnungspolitischen Rahmens und auch die konkrete Regulierung in den verschiedenen EU-Mitgliedstaaten mittlerweile relativ stark angeglichen haben bzw. diese angeglichen wurden (vgl. Kiesewetter 2007), ist die Regulierung der Energiewirtschaft und somit auch der Liberalisierungsgrad zwischen den EU-Mitgliedstaaten noch sehr unterschiedlich (vgl. Hense und Schäffner 2004; London Economics 2007). Diese bis heute andauernde Heterogenität von Regulierungsregeln im Bereich der Elektrizitätswirtschaft resultiert einerseits aus den unterschiedlichen historischen Gegebenheiten, und andererseits auch aus der im Jahre 1997 erlassenen Strombinnenmarktrichtlinie (1996/92/EG), welche den EU-Mitgliedstaaten zunächst nur eine schrittweise Einführung des Wettbewerbs auf den Energiemärkten vorgeschrieben hat. In diesem Zuge ist es den einzelnen Mitgliedstaaten selbst überlassen worden, ihre Märkte ggf. über das Maß der vorgegebenen Mindestanforderungen hinaus für den Wettbewerb zu öffnen. Auch in der konkreten Ausgestaltung des ordnungspolitischen Rahmens wurde den Mitgliedstaaten zunächst relativ weitgehende Freiheiten zugestanden [...]

Measuring the relationship between supervisory authorities and banks: An assessment of the German banking sector - Paul, Stephan; Stein, Stefan; Uhde, André (Journal of Risk Managment in Financial Institutions)
The successful implementation of a harmonised regulatory framework for the global banking system is still a long way off. This mainly results from (a) different traditions in banking regulation and supervision at the national level, (b) different national emphases on regulatory sub-goals such as efficiency or the protection and promotion of national financial markets, and (c) different institutional settings and conditions. In this context, studies on the banking industry's assessment of supervisory processes and instruments highlight how effectively and efficiently individual nation states are implementing international frameworks such as Basel II and the Capital Requirements Directive for Europe. In November 2005, the German Government commissioned an evaluation of the supervisory processes and instruments of the country's banking authorities, BaFin and Bundesbank. The study aimed to determine the options for further optimising supervision, reducing regulatory burden and bureaucracy, and otherwise restricting supervision. This paper presents the most important findings from the survey, analyses significant differences in assessments given by various banking groups, empirically evaluates significant drivers of banks' overall satisfaction with banking supervision, and drafts proposals for improving banking regulation and supervision in Germany. Finally, aspects of further research are discussed.
Keywords: banking supervision; quality; assessment; banking sector

Vertikale Entflechtung netzgebundener Industrien: Kosten und Nutzen aus ökonomischer Sicht - Haucap, Justus; Heimeshoff, Ulrich; Uhde, André (Gesellschaft für öffentliche Wirtschaft)
Die in den letzten 25 Jahren weltweit und in Europa in den letzten zehn Jahren forcierte Liberalisierung der Telekommunikationsbranche stellt ein bemerkenswertes Beispiel für den erfolgreichen Wandel ordnungspolitischer Rahmenbedingungen dar. Die Erfolge dieser Reformprozesse sowie die daraus resultierenden institutionellen Lernprozesse waren auch für die übrigen netzgebundenen Industrien wie z.B. Energiewirtschaft, Bahn oder Post wegweisend. Thema dieses Aufsatzes ist das Spannungsfeld zwischen der Vermeidung von Diskriminierungsanreizen durch vertikale Separierung, möglichen Effizienzgewinnen und adäquaten Investitionsanreizen. Im Folgenden werden sowohl theoretische Grundlagen netzgebundener Industrien im Allgemeinen als auch theoretische Argumente für oder gegen eine vertikale Integration netzgebundener Industrien diskutiert. Die theoretischen Argumente werden anschließend beispielhaft auf den Bahnsektor, die Energiewirtschaft sowie die Wasserwirtschaft angewendet.

Selbstregulierungspotenzial in der Kreditwirtschaft : eine vertragstheoretische und evolutionsökonomische Analyse - Uhde, André

Credible Threats as an Instrument of Regulation for Network Industries - Haucap, Justus; Heimeshoff, Ulrich; Uhde, André (REGULATORY CHANGES, INNOVATIONS AND INVESTMENT DYNAMICS IN THE DIGITAL WORLD ECONOMY)
In order to avoid over-regulation, some countries have experimented with what might be called threat-based regulation. The idea is - similarly to the contestable market model - that actual regulation may not be necessary as long as the threat of regulation is credible. In that case, so the idea, even monopolies will abstain from setting monopolistic prices in order to avoid being regulated. As experience from Germany and New Zealand has demonstrated, there are quite a number of problems associated with threat-based regulatory systems. The most significant problem has turned out to be the likely under-regulation and according welfare losses from market power, and in this context, a critical issue that has been identified is the credibility of the regulatory threat. If the threat of regulation is not credible, a light-handed regulatory regime (LHRR) amounts to leaving monopolistic firms unregulated, clearly an undesirable situation from a welfare point of view. This failure of threat-based regulatory systems results from potential free-rider problems associated with good corporate behaviour (as in the case of Germany's electricity market) as well as the lack of credibility of the threat either because of the weakness of the enforcement authorities or due to political constraints. Furthermore, a problem emerges if exercising the threat of regulation implies an abandonment of the LHRR and a corresponding substitution with heavy-handed ex ante regulation. An innovative way out of this dilemma has been the quasi-automatic threshold system originally designed for New Zealand's electricity distribution networks, which aims at simulating the pressures that companies would face in competitive markets.
Keywords: light-handed regulation; network industries; electricity; telecommunications

Besonderheiten und Wettbewerbsprobleme des Marktes für wissenschaftliche Fachzeitschriften - Haucap, Justus; Hartwich, Tobias; Uhde, André (Vierteljahrshefte zur Wirtschaftsforschung)
ie Preise für wissenschaftliche, technische und medizinische (WTM) Fachzeitschriften sind in den letzten 20 Jahren dramatisch gestiegen. Die unterschiedlichen Preisentwicklungen zwischen kommerziellen und nichtkommerziellen Verlagen ist dabei nicht durch unterschiedliche Kostenentwicklungen zu erklären. Vielmehr haben die forschungsorientierten Top-Journale Marktmacht, da sie den Charakter positionaler Güter haben, die von Bibliotheken nur sehr schwer substituiert werden können, sodass streng genommen aufgrund der Einzigartigkeit jedes einzelnen Artikels jede Top-Zeitschrift einen eigenen Markt konstituiert. Top-Zeitschriften haben aus drei Gründen einen erheblichen Preissetzungsspielraum: Erstens sind der Markteintritt und die Ablösung teurer Top-Journale aufgrund des Koordinationsproblems zwischen Autoren, Gutachtern und Bibliotheken für neue Zeitschriften sehr schwierig. Zweitens haben Bibliotheken Wechselkosten (durch die Tendenz, vollständige Reihen zu beziehen). Drittens ist die Nachfrage auch aufgrund der kollektiven Entscheidungsfindung in Bibliotheken relativ unelastisch. Ein effektiver Ausweg, der die Verlage disziplinieren würde, könnte die konzertierte Aktion von Forschungsgemeinschaften sein, die ihre Mitarbeiter oder die von ihnen finanziell geförderten Wissenschaftler verpflichten, ihre Artikel und Forschungsergebnisse kostenfrei oder zumindest zu günstigen Konditionen zur Verfügung zu stellen.

Diskussion von Ordnungsrahmen einer zukünftigen internationalen Bankenregulierung - Uhde, André (Globale Wirtschaft u. nationale Verantwortung, Forschungsergebnisse im Überblick, X. Kongress „Junge Wissenschaft und Wirtschaft“ der Hanns Martin Schleyer-Stiftung)

Diskussion von Ordnungsrahmen einer zukünftigen internationalen Bankenregulierung - Michalak, Tobias C.; Uhde, André (Globale Wirtschaft u. nationale Verantwortung, Forschungsergebnisse im Überblick, X. Kongress „Junge Wissenschaft und Wirtschaft“)